The role of muscleblind-like proteins in myotonic dystrophy - Arya, Sukrat (2014)
Myotonic dystrophy (DM) is a progressive multisystemic genetic disorder which is inherited as an autosomal dominant trait. There are two subtypes of the disorder, DM type 1 and DM type 2. DM type1 is caused by an expansion of a CTG repeat located in the 3' untranslated region of the DMPK gene on chromosome 19q13.3, whereas DM type 2 is caused by a CCTG expansion in intron 1 of ZNF9 gene located on chromosome 3q. The mutant RNAs containing the expanded CTG/CCTG repeats alters the activity of various alternative splicing factors like Muscleblind-like (MBNL) proteins, which are sequestered in the ribonuclear foci in nucleus by the expanded mutant transcripts resulting in a number of splicing defects observed in DM patients.